Investigation of the Role of Protein Kinase D in Human Rhinovirus Replication - Guedan,A; Swieboda,D; Charles,M; Toussaint,M; Johnston,SL; Asfor,A; Panjwani,A; Tuthill,TJ; Danahay,H; Raynham,T; Mousnier,A; Solari,R (Journal of Virology, 2017)
Picornavirus replication is known to cause extensive remodeling of Golgi and endoplasmic reticulum membranes, and a number of the host proteins involved in the viral replication complex have been identified, including oxysterol binding protein (OSBP) and phosphatidylinositol 4-kinase III beta (PI4KB). Since both OSBP and PI4KB are substrates for protein kinase D (PKD) and PKD is known to be involved in the control of Golgi membrane vesicular and lipid transport, we hypothesized that PKD played a role in viral replication. We present multiple lines of evidence in support of this hypothesis. First, infection of HeLa cells with human rhinovirus (HRV) induced the phosphorylation of PKD. Second, PKD inhibitors reduced HRV genome replication, protein expression, and titers in a concentration-dependent fashion and also blocked the replication of poliovirus (PV) and foot-and-mouth disease virus (FMDV) in a variety of cells. Third, HRV replication was significantly reduced in HeLa cells overexpressing wild-type and mutant forms of PKD1. Fourth, HRV genome replication was reduced in HAP1 cells in which the PKD1 gene was knocked out by clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9. Although we have not identified the molecular mechanism through which PKD regulates viral replication, our data suggest that this is not due to enhanced interferon signaling or an inhibition of clathrin-mediated endocytosis, and PKD inhibitors do not need to be present during viral uptake. Our data show for the first time that targeting PKD with small molecules can inhibit the replication of HRV, PV, and FMDV, and therefore, PKD may represent a novel antiviral target for drug discovery.